Self-Assembly MXene-rGO/CoNi Film with Massive Continuous Heterointerfaces and Enhanced Magnetic Coupling for Superior Microwave Absorber - Li, Xiao; Wu, Zhengchen; You, Wenbin; Yang, Liting; Che, Renchao (Nano-micro letters, 2022)
Highlights The rGO/CoNi nanosheets embedded between the MXene layers can continue to serve as a conductive channel, ensuring carrier migration and proper conductive loss capability. Owing to the strong magnetic coupling between the magnetic FeCo alloy nanoparticles on the rGO substrate, the entire MXene-rGO/CoNi film exhibits a strong magnetic loss capability. Self-assembly MXene-rGO/CoNi films hold excellent microwave absorption performance − 54.1 dB at 13.28 GHz. MXene, as a rising star of two-dimensional (2D) materials, has been widely applied in fields of microwave absorption and electromagnetic shielding to cope with the arrival of the 5G era. However, challenges arise due to the excessively high permittivity and the difficulty of surface modification of few-layered MXenes severely, which infect the microwave absorption performance. Herein, for the first time, a carefully designed and optimized electrostatic self-assembly strategy to fabricate magnetized MXene-rGO/CoNi film was reported. Inside the synthesized composite film, rGO nanosheets decorated with highly dispersed CoNi nanoparticles are interclacted into MXene layers, which effectively suppresses the originally self-restacked of MXene nanosheets, resulting in a reduction of high permittivity. In addition, owing to the strong magnetic coupling between the magnetic FeCo alloy nanoparticles on the rGO substrate, the entire MXene-rGO/CoNi film exhibits a strong magnetic loss capability. Moreover, the local dielectric polarized fields exist at the continuous hetero-interfaces between 2D MXene and rGO further improve the capacity of microwave loss. Hence, the synthesized composite film exhibits excellent microwave absorption property with a maximum reflection loss value of − 54.1 dB at 13.28 GHz. The electromagnetic synergy strategy is expected to guide future exploration of high-efficiency MXene-based microwave absorption materials.